2005
DOI: 10.1359/jbmr.050609
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Osteopenic Women at High Risk of Fracture: The OFELY Study

Abstract: About one-half of women with incident fractures have BMD above the WHO diagnostic threshold of osteoporosis. In the OFELY study, low BMD, increased markers of bone turnover, and prior fracture could be used to identify, within osteopenic women, those at high risk of fracture.Introduction: Recent data suggest that about one-half of women with incident fractures have BMD above the World Health Organization (WHO) diagnostic threshold of osteoporosis (T score Յ −2.5). We aimed to identify, within osteopenic women,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
162
0
30

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 342 publications
(198 citation statements)
references
References 43 publications
6
162
0
30
Order By: Relevance
“…Epidemiological studies have demonstrated that a significant number of individuals with incident osteoporotic fractures have BMD values above the WHO diagnostic threshold of osteoporosis (T-score≥−2.5) [9][10][11][12]. Findings of a recent study indicate that at any given BMD T-score, the risk of incident vertebral, non-vertebral, and any fracture depended heavily on prevalent radiographic vertebral fracture status.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have demonstrated that a significant number of individuals with incident osteoporotic fractures have BMD values above the WHO diagnostic threshold of osteoporosis (T-score≥−2.5) [9][10][11][12]. Findings of a recent study indicate that at any given BMD T-score, the risk of incident vertebral, non-vertebral, and any fracture depended heavily on prevalent radiographic vertebral fracture status.…”
Section: Discussionmentioning
confidence: 99%
“…Although patients with lower BMD are at high risk of fractures, studies have shown that the largest number of osteoporotic fractures occurred among those with osteopenia (BMD -1 to -2.5) 3637. This can be explained by the presence of larger number of subjects with osteopenia than with osteoporosis and therefore even with a lower risk for fractures, the number of fractures can be substantial.…”
Section: Osteopenia and Fracturesmentioning
confidence: 99%
“…Research aimed at establishing composite algorithms that include several risk determinants for the prediction of future fractures is under way (Cummings et al 1995, De Laet et al 1998, Sornay-Rendu et al 2005) but as far as we know, the contribution of multiple fractures as opposed to single fractures has not been considered to date.…”
Section: Fracture Prediction: Relative and Combined Contributions Fromentioning
confidence: 99%